Impact of a Central Scaffold on the Binding Affinity of Fragment Pairs Isolated from DNA‐Encoded Self‐Assembling Chemical Libraries. (20th October 2017) - Bigatti, Martina; Dal Corso, Alberto; Vanetti, Sara; Cazzamalli, Samuele; Rieder, Ulrike; Scheuermann, Jörg; Neri, Dario; Sladojevich, Filippo
Abstract: The screening of encoded self‐assembling chemical libraries allows the identification of fragment pairs that bind to adjacent pockets on target proteins of interest. For practical applications, it is necessary to link these ligand pairs into discrete organic molecules, devoid of any nucleic acid component. Here we describe the discovery of a synergistic binding pair for acid alpha‐1 glycoprotein and a chemical strategy for the identification of optimal linkers, connecting the two fragments. The procedure yielded a set of small organic ligands, the best of which exhibited a dissociation constant of 9.9 nm, as measured in solution by fluorescence polarization. Abstract : The missing link : The screening of encoded self‐assembling chemical libraries allows the identification of fragment pairs that bind to adjacent pockets on target proteins of interest. For practical application, these ligand pairs must be linked into discrete organic molecules, devoid of any nucleic acid component. Here we describe the discovery of a synergistic binding pair for acid alpha‐1 glycoprotein and a chemical strategy for the identification of optimal linkers, connecting the two fragments.